(untitled) (Global Journal of Computer Science and Technology, 2024)
In almost every way web development has been getting better and better over the last ten years During this time a number of frameworks and libraries came out which made it much easier and faster to make a web app Over the last decade the LAMP stack Linux Apache MySQL and PHP and Java-based applications have dominated web development It was challenging for a single developer to construct a web application by using these stacks because of how complex they were As the field of web development matured MERN-an acronym for MongoDB Express React and Node JS -emerged as the dominant stack in 2023 Due to the relative simplicity of the technologies comprising this stack a single developer may effectively handle both the front-end and back-end of the application MongoDB which is a no-SQL database Express which is a framework of Node JS used in back-end development React which is a JavaScript library used in front-end development and NodeJS which is an environment for JavaScript these are the components that make up the MERN stack The main goal of this thesis is to learn about the MERN stack and build a fully working multi-vendor e-commerce web application that is a laptop reselling platform This application has a user-friendly interface sign-up and login systems that are JWT JSON Web Token secured JWT is used to protect every API that this app uses So that users don t have any problems it s now easier to buy and sell used laptops The interface and functionality of this app are designed with the user s ease of use in mind The beta version of this is already completed and hosted in the server